Family dissolution and public policies in the United States: Social provisions and institutional changes since the 1980s - Britta Grell (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
As a consequence of changing patterns of family formation and dissolution in the western world, national welfare institutions confront new demands to accommodate such issues as disproportionate poverty risks among single-mother families, increased requirements for non-parental child care arrangements, and the regulation of child maintenance and support. This paper documents and analyzes the most important social and legal provisions and changes in the United States since the 1980s with implications for the well-being of separated parents and their children, starting with alimony reform legislation to maternity and parental leave programs. It concludes that compared to Germany the institutional and financial support of lowincome custodial parents, the majority of whom are women, is still rather limited. While family-friendly policies - most of them based on employment and the tax system - have been expanded since the 1980s, the US welfare systems provides less financial and legal assistance to vulnerable families with children.
Keywords: 300; Familiensoziologie; Scheidung; Familienpolitik; Soziale Sicherung; Fraueneinkommen; USA